1986
DOI: 10.1073/pnas.83.16.6112
|View full text |Cite
|
Sign up to set email alerts
|

Human parathyroid antigen: characterization and localization with monoclonal antibodies.

Abstract: A cell surface antigen on human parathyroid cells was identified by monoclonal antibodies. The antigen, called parathyroid antigen (PTA), is found on both of two major polypeptides (190 kDa and 160 kDa) apparently associated exclusively with parathyroid cells. To determine whether PTA was a suitable target for in vivo imaging, 125I-labeled anti-PTA was injected into nude mice bearing human parathyroid xenografts. IgG1 anti-PTA antibody showed excellent radiolocalization of the grafts, whereas IgM anti-PTA, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…From this study and the reports of Posillico's group [1] and our group [2], however, it can be concluded that the parathyroid cell has a variety of surface molecules, some of which are shared by other endocrine tissues, others of which appear unique to the parathyroid cell, and others of which are restricted to the parathyroid and kidney. For many of these reported markers, specific monoclonal antibody binding can affect parathyroid hormone release and/or cellular calcium changes.…”
supporting
confidence: 39%
“…From this study and the reports of Posillico's group [1] and our group [2], however, it can be concluded that the parathyroid cell has a variety of surface molecules, some of which are shared by other endocrine tissues, others of which appear unique to the parathyroid cell, and others of which are restricted to the parathyroid and kidney. For many of these reported markers, specific monoclonal antibody binding can affect parathyroid hormone release and/or cellular calcium changes.…”
supporting
confidence: 39%
“…At present, we do not know whether the monoclonal antiparathyroid antibody recently reported by Cance et al [18] recognizes similar structures as the presently used antibodies. The former antibody appears to react exclusively with parathyroid cells and its functional effects has not been reported on.…”
Section: Discussionmentioning
confidence: 88%
“…Previous authors have described successful intramuscular parathyroid tissue implantation through a skin incision 2,8,9 . The technique of implantation used in the present study differed in that the tissue was injected intramuscularly into the mouse's flank.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Previous authors have described successful intramuscular parathyroid tissue implantation through a skin incision. 2,8,9 The technique of implantation used in the present study differed in that the tissue was injected intramuscularly into the mouse's flank. To do this, a 1 3 l-mm to 1 3 2-mm fragment of tissue was drawn up into the hub of a 1Cgauge needle and was injected into the muscle.…”
Section: Experiments 1: Mansplantation Of Human Parathyroid Tissuementioning
confidence: 99%
See 1 more Smart Citation